Compact and Wide Upper-Stopband Triple-Mode Broadband Microstrip BPF - Wen Chen Wen Chen; Yongjiu Zhao; ZhouxiaoJun ZhouxiaoJun (Universitas Ahmad Dahlan, 2012)
A broadband microstrip bandpass filter (BPF) with compact size, sharp skirt and wide upper-stopband performance is proposed using the triple-mode stub-loaded resonator. The resonator can generate one odd mode and two even modes in the desired passband. Due to the main path signal counteraction, two transmission zeros Tz1, Tz2 can be created near the passband edge to achieve sharp skirt. Two transmission zeros Tz4, Tz5 are created between two harmonic frequencies hm2, hm3 by the folded open stub and the interdigital coupling feeding lines, respectively. Owing to the source-load coupling, one zero Tz3 is introduced to deepen the stopband. Meanwhile, the zero Tz1 is shifted to the lower cut-off frequency and the other three ones Tz2, Tz4, Tz5 can be slightly turned to suppress three harmonic frequencies hm1, hm2, hm3. One filter prototype with the fractional bandwidth 34% is designed, fabricated and measured.